ANALISIS KINERJA SISTEM INFORMASI AKUNTANSI DALAM MENGOPTIMALKAN PERSEDIAAN SEPEDA MOTOR PADA DEALER PT. SUMBER JADI KENCANA MOTOR - Saskia, Aini; Melisa Amelia, Mekar; Reza Septriawan, Muhammad (PT. ANAN PUBLISHER CENDEKIA, 2025)
This study aims to analyse the performance of accounting information systems in optimising motorcycle inventory management at PT Sumber Jadi Kencana Motor dealer. In an era of increasingly fierce competition, efficient inventory management is the key to improving operational performance and customer satisfaction. The research method used is a qualitative approach with data collection through interviews, observation, and document analysis related to the accounting information system implemented at the dealership. The results show that although the existing accounting information system has made a positive contribution to inventory management, there are several obstacles that hinder optimisation, such as data input errors, lack of user training, and communication problems between head office and dealers. This study recommends improvements in user training, enhancement of system features for data update automation, as well as strengthening internal communication to minimise errors and improve the accuracy of inventory information. Thus, this research is expected to contribute to the development of a more effective accounting information system in supporting inventory management at PT Sumber Jadi Kencana Motor.